1991
DOI: 10.1104/pp.97.3.851
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Aspects of the Inorganic Carbon-Concentrating Mechanism in Cyanobacteria

Abstract: This paper reviews progress made in elucidating the inorganic carbon concentrating mechanism in cyanobacteria at the physiological and molecular levels. Emphasis is placed on the mechanism of inorganic carbon transport, physiological and genetical analysis of high-CO2-requiring mutants, the polypeptides induced during adaptation to low C02, the functional significance of carboxysomes, and the role of carbonic anhydrase. We also make occasional reference to the green algal inorganic carbon-concentrating mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 24 publications
5
88
0
1
Order By: Relevance
“…This result is consistent with similar findings using the )'Rb+\valinomycin method (Ritchie et al, 1996). Transient hyperpolarization, based upon the use of lipophilic cation probes, has also been reported after inorganic carbon has been added to blue-green algal cells (Kaplan et al, 1982 ;Miller et al, 1984 ;Zenvirth et al, 1984 ;Kaplan et al, 1989 ;Miller et al, 1990 ;Kaplan et al, 1991). Chlorophyll fluorescence changes in response to added HCO $ − have also been interpreted as reflecting hyperpolarization of the membrane (Miller & Canvin, 1987 ;Miller et al, 1988).…”
Section: supporting
confidence: 80%
See 1 more Smart Citation
“…This result is consistent with similar findings using the )'Rb+\valinomycin method (Ritchie et al, 1996). Transient hyperpolarization, based upon the use of lipophilic cation probes, has also been reported after inorganic carbon has been added to blue-green algal cells (Kaplan et al, 1982 ;Miller et al, 1984 ;Zenvirth et al, 1984 ;Kaplan et al, 1989 ;Miller et al, 1990 ;Kaplan et al, 1991). Chlorophyll fluorescence changes in response to added HCO $ − have also been interpreted as reflecting hyperpolarization of the membrane (Miller & Canvin, 1987 ;Miller et al, 1988).…”
Section: supporting
confidence: 80%
“…Many of the reported membrane potential determinations for blue-green algae are based solely on the use of lipophilic cation probes (Kaplan et al, 1980 ;Reed et al, 1980 ;Zdrou & Tromballa, 1981 ;Kaplan et al, 1982 ;Miller et al, 1984 ;Reinhold et al, 1984 ;Zenvirth et al, 1984 ;Kaplan, 1985 ;Peschek et al, 1985 ;Budd & Kerson, 1987 ;Kaplan et al, 1989Kaplan et al, , 1991. Some of the above studies did not take proper account of the extensive binding of lipophilic cations to the surfaces of cells and so their estimates of the membrane potential are inaccurate.…”
Section: mentioning
confidence: 99%
“…In plants, intracellular CA enhances the rate of CO # to HCO − $ conversion, for fixation by phosphoenolpyruvate carboxylase . CA has been proposed to be involved in C i utilization in most anaerobic bacteria and archaea (Alber & Ferry, 1994 ;Kaplan et al, 1991). CA function in processes other than C i utilization has also been verified in several bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of several sites within the genomic region of rbc in Synechococcus PCC 7942, including rbcS, resulted in high C02-requiring mutants (9,13,20). It was, therefore, suggested that this region contains a cluster of genes, the products of which are involved in various functions of the Ci-concentrating mechanism and, hence, in the ability of cyanobacteria to grow in the presence of low CO2.…”
Section: Discussionmentioning
confidence: 99%
“…When transferred from high-to low-CO2 conditions, the cells undergo an adaptation process that includes the induction of a Ci-concentrating mechanism. As a consequence of this increase in the ability to accumulate Ci internally, the apparent photosynthetic affinity for extemal Ci is 10-to 20-fold higher in low than in high C02-grown cells (1,3,8,9,14,18 Cultures of Synechococcus sp. strain PCC 7942 and the mutants obtained following modifications of this strain were grown in the presence of high (5% C02 in air) or low (air) levels of C02 as previously described (12).…”
Section: Methodsmentioning
confidence: 99%